2019
DOI: 10.1177/0300060519860969
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of an invasive versus conservative strategy in patients aged ≥80 years with acute ST-segment elevation myocardial infarction

Abstract: Objective To investigate what is the most appropriate strategy for patients with ST-segment elevation myocardial infarction (STEMI) aged ≥80 years in China. Methods This cohort study retrospectively enrolled patients with STEMI aged ≥80 years old and grouped them according to the treatment strategy that was used: a conservative treatment strategy or an invasive treatment strategy. Factors associated with whether to perform an invasive intervention, in-hospital death and a good prognosis were investigated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(49 reference statements)
2
2
1
2
Order By: Relevance
“…Similarly, high Killip class (III & IV) did not show statistically significant data as independent risk factor for in-hospital mortality after P-PCI in elderly population. Those figures were not matching with data for Killip III & IV from previous studies [30,34]. However, it could be argued that the population sample of those studies were smaller and younger than the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, high Killip class (III & IV) did not show statistically significant data as independent risk factor for in-hospital mortality after P-PCI in elderly population. Those figures were not matching with data for Killip III & IV from previous studies [30,34]. However, it could be argued that the population sample of those studies were smaller and younger than the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Arterial hypertension and CKD were the only variables demonstrated to be independent risk factors for in-hospital mortality after P-PCI in elderly patients with STEMI. Findings were consistent with previous studies that demonstrated that absence of hypertension and low creatinine levels could provide better clinical outcomes [11,29,30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a considerable research, Sui found that octogenarians have a greater risk of mortality and heart failure during the first months following the AMI. But, after a few months, the prognosis of the elderly patients became similar to that of those aged <80 years [24]. In our study, the analysis of the Kaplan-Meier 1-year mortality and 1-year readmission curves suggest a rather uniform time-distribution of the events in both AMI age-categorized patients.…”
Section: Discussionsupporting
confidence: 59%
“…Ишемическая болезнь сердца (ИБС) занимает лидирующие позиции в структуре заболеваемости и смертности населения развитых стран мира [17]. Благодаря достижениям современной медицины, своевременной доступности методов реваскуляризации миокарда, включающим тромболитическую терапию и инвазивные методы лечения [14,21], уменьшается количество летальных исходов в острый период инфаркта миокарда с подъемом сегмента ST (ИМпST) [4,6,13], и как следствие, наблюдается увеличение выживаемости пациентов после перенесенного ИМпST, включая больных пожилого и старческого возраста [7, 10,12].…”
unclassified